Pembangunan Destinasi Pariwisata di Kelurahan Muara Enim Melalui Pendekatan Pengembangan Kampung Wisata - Fadlina, Siti (Jurnal Ilmiah Pariwisata, 2021)
Developments and in the era of globalization have brought changes in tourist motivation in choosing tourist attractions which gave birth to rural tourism that presents community life, culture, and local wisdom. This study aims to analyze the components of the Muara Enim tourist village, analyze the classification of the Muara Enim tourist village, analyze the potential and problems of Muara Enim tourism. This research method uses qualitative research with primary data collection using observation and surveys with interviews. Then secondary data collection uses various sources of agencies and literature such as print and electronic media, laws and regulations, statistical data, and others. Respondents in this study were 10 resource persons at the district government level, the Kelurahan Office, as well as Groups, Forums, and Community Self-Help Agencies in Muara Enim Village. The results of the research from the assessment of the components of the tourist village already have a basic capital as a seed which is still low at 21.2%. Therefore, support from the community, government and other stakeholders is needed to fulfill the standardization of tourist villages and improve aspects of tourism development so that Muara Enim Village can be developed into a Tourism Village. Keywords: Muara Enim Village, Tourism Destination, Tourism Village